Contribution of swimming, cycling and running in the final performance in different distances of triathlon races - Scorcine, C.; Pereira, R.; Madureira, F.; Colantonio, E. (MOJ Sports Medicine, 2017)
The aim of the study was to analyze which modality (swimming, cycling or running) may interfere significantly to the final performance of different triathlon events. The present study observed the last five results of Olympic Distance, Half Distance and Full Distance (Ironman) of World Championship from 2010 to 2015. The athlete`s times were tabulated separate per: swimming time, cycling time, running time and total time. The sample was divided in two groups: (G1) athletes who were classified among the five best of each step and (G2) the athletes classified between sixth and tenth place. The total sample was composed by male and female athletes (N=300). Statistical analysis: the regression, correlation and comparison model was used between two groups for the three distances of triathlon tests and for all investigated variables. The results pointed that for each type of test and athlete one modality may be more deterministic to the final performance. Therefore, the training programs should consider that triathlon is one only modality; thus, the training planning should be focused in a unique way taking into account the specificity of race.